Non-Life Insurance Distribution Channels in Poland Compared to Selected European Countries - Anna SZYMAŃSKA (Communications of International Proceedings, 2020)
Increased competitiveness on the insurance market forces insurance companies to change their sales strategy. The development of domestic insurance markets and consumer preferences directly affect both the models of distribution of insurance services operating in them and the directions of changes in the structure of these channels. The aim of the paper is to compare the non-life insurance sales models in Poland with selected European countries. A research hypothesis was made that models of non-life insurance distribution channels on domestic European markets can be distinguished. Research results indicate three groups of countries in Europe with a similar level of development of non-life insurance markets. Four models of insurance sales have been distinguished on the market.
Keywords: Non-Life Insurance; Insurance Distribution.